Assessing the suitability of digital advertising formats for products from diverse business sectors: Insights from experts - Vaida Zemlickienė; Isabel Palomo-Domínguez; Zenonas Turskis; Indrė Lapinskaitė (Contemporary Economics, 2025)
Different companies need to spread the word about products; advertising agencies need to make rational decisions, simplify decision-making, find the best alternative, and increase the reach of potential users. While demographic, geographic, etc. factors are recognized when selecting advertising tools, there's a scarcity of studies tailored to the suitability of digital advertising formats for products in a specific category. The existing studies provide insights into ways to improve the effectiveness of individual digital advertising formats but are of limited use for strategic decision-making. This study assumes that some digital advertising formats are more suitable for products from different business sectors than others. The primary objective is to assess the suitability of digital advertising formats for different products categories. To achieve this objective, digital advertising formats and business sectors were categorized after delving into content and relevance. Surveying advertising experts in Spain, the study employs MCDA method to summarize outcomes. The research findings reveal that advertisement formats like Search Engine Marketing and Online Behavioral Advertising are deemed most suitable across all sectors. Conversely, the Advergames exhibits the lowest assessment for the Hygiene and Public Services. In-game advertising also got the lowest rating, primarily within the Hygiene and Public Services sector. At the same time, Merchandising of Famous Figures in a Virtual World receives a less favourable evaluation, particularly within the Financial Services sector. The research findings offer valuable guidelines for decision-makers in advertising, aiding in campaign strategic planning and identifying the most expedient digital advertising formats for products across diverse sectors.
Keywords: M37; C44; 330; determination of suitability; digital advertising formats; products from different business sectors; MCDA